2016
DOI: 10.1038/nmicrobiol.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dynamics of the preterm infant gut microbiota and antibiotic resistome

Abstract: Development of the preterm infant gut microbiota is emerging as a critical research priority1. Since preterm infants almost universally receive early and often extended antibiotic therapy2, it is important to understand how these interventions alter gut microbiota development3-6. Analysis of 401 stools from 84 longitudinally sampled preterm infants demonstrates that meropenem, cefotaxime and ticarcillin–clavulanate are associated with significantly reduced species richness. In contrast, vancomycin and gentamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
391
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 378 publications
(420 citation statements)
references
References 44 publications
29
391
0
Order By: Relevance
“…Given that 98.7% of all reads mapped to 12 reconstructed bacterial and 18 phage/plasmid genomes from Infant 1, and 95.0% to 14 bacterial and 21 phage/plasmid genomes from Infant 2, we conclude that the majority of the community was accounted for. This result confirms the overall low diversity of the early community when compared to full-term infants Gibson et al 2016;Ward et al 2016). Overlap of strains across body sites contributes to the low total diversity of these premature infant microbiomes compared to those of other infants.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Given that 98.7% of all reads mapped to 12 reconstructed bacterial and 18 phage/plasmid genomes from Infant 1, and 95.0% to 14 bacterial and 21 phage/plasmid genomes from Infant 2, we conclude that the majority of the community was accounted for. This result confirms the overall low diversity of the early community when compared to full-term infants Gibson et al 2016;Ward et al 2016). Overlap of strains across body sites contributes to the low total diversity of these premature infant microbiomes compared to those of other infants.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have described the gut microbiome of premature infants as relatively simple and prone to rapid changes in composition Gibson et al 2016;Ward et al 2016). To our knowledge, this is the first study to investigate the body habitat range of individual genotypes and to compare microbial activity of the same populations across body sites.…”
Section: Discussionmentioning
confidence: 92%
“…The importance of microbiota to human health and disease has come into the scientific spotlight within the last decade, [18][19][20][21][22] and major questions surround how and when we acquire our microbiota. [23][24][25][26][27] It is widely recognized that microbial transmission of bacteria from mother to offspring is essential for the establishment and development of a healthy nascent microbiome, which may impact infant growth, [28][29][30] immune system maturation [31][32][33][34][35] and even neurodevelopment. 36,37 Interestingly, emerging evidence has additionally indicated that transmission of microbiota from mother to offspring may occur before delivery, which has since reemphasized the importance of the pregnancy period to the development of the neonatal microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Gibson et al recently used this suite of techniques to develop a sequence-unbiased account of the effects of antibiotic therapy on the preterm infant microbiota with respect to phylogeny and antibiotic resistance gene distribution. 37 A longitudinal, sequencing based interrogation of the preterm infant gut microbiota…”
Section: Introductionmentioning
confidence: 99%